Um Sistema de Detecção de Intrusão para Detecção de Ataques de Negação de Serviço na Internet das Coisas. - SOUSA, Breno Fabrício Lira Melo (2016)
The paradigm of the Internet of Things (in english, Internet of Things - IoT) came to allow intercommunication between different objects via Internet, and thereby facilitate the form of how the end user will interact with a wide variety of devices that surround him in everyday life. The availability of features that these devices have is a factor that deserves great attention because the use of such resources inappropriately can cause serious damage. Therefore, since such devices are connected to the internet, they are vulnerable to various threats, such as, denial-of-service attack (DoS). In order to tackle DoS type threats in IoT, an Intrusion Detection System (IDS) is proposed for IoT, aiming at detecting some types of DoS attacks.